eCM 2008
DOI: 10.22203/ecm.v015a05
|View full text |Cite
|
Sign up to set email alerts
|

Bone development and its relation to fracture repair. The role of mesenchymal osteoblasts and surface osteoblasts

Abstract: Bone development occurs by two mechanisms: intramembranous bone formation and endochondral bone formation. Bone tissue forms by eventual differentiation of osteoprogenitor cells into either mesenchymal osteoblasts (MOBL), which synthesize woven bone in random orientation, or surface osteoblasts (SOBL), which synthesize bone on surfaces in a well oriented lamellar array. Bone repair uses the same formation patterns as bone development but the specific mechanism of repair is determined by the biomechanical envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
345
0
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(384 citation statements)
references
References 67 publications
(40 reference statements)
7
345
0
21
Order By: Relevance
“…On the other hand, during bone development, cellular differentiation into bone forming osteoblasts occurs within a soft matrix in the range of 100−1000 Pa shear modulus. 64,65 Previous studies also showed that in vitro osteogenic differentiation can be supported on soft hydrogel matrices, which have similar stiffness to developing bone. 66,67 The gene expression results obtained from PA/PEG composite system also pointed to similar conclusions showing that the optimal design of a material for the desired cellular outcome requires the consideration of multiple factors since cells can sense complex niche cues, and these signals can direct cell fate in an interactive manner.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…On the other hand, during bone development, cellular differentiation into bone forming osteoblasts occurs within a soft matrix in the range of 100−1000 Pa shear modulus. 64,65 Previous studies also showed that in vitro osteogenic differentiation can be supported on soft hydrogel matrices, which have similar stiffness to developing bone. 66,67 The gene expression results obtained from PA/PEG composite system also pointed to similar conclusions showing that the optimal design of a material for the desired cellular outcome requires the consideration of multiple factors since cells can sense complex niche cues, and these signals can direct cell fate in an interactive manner.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…As a characteristic long bone, the tibia is derived from the mesenchymal tissue of limb buds and ossifies via endochondral bone formation during weeks 7 and 12 of fetal development (Shapiro;Lee et al, 2013). The structural stages in the formation of the tibial diaphyseal and epiphyseal regions are characterized by the presence and apposition of the primary and secondary ossification centers, respectively (Shapiro).…”
Section: Discussionmentioning
confidence: 99%
“…proximal and distal ends and a shaft (Standring; Moore et al). The nutrient foramen, which is situated obliquely at the superior end of the vertical line on the posterior surface, provides entry into the medullary cavity (Shapiro, 2008;Moore et al;Kulkarni, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 On a histologic level, tension has been demonstrated to reorient collagen fibrils parallel to the axis of stress. 79,80 On a genetic level, mechanical shear stress has been shown to cause an upregulation of 'antifibrotic' genes. 81 In the first published pilot study on traction therapy for PD, Levine et al 82 evaluated 11 men with PD, 8 had failed non-surgical treatments.…”
Section: Penile Electroshock Wave Therapy (Eswt)mentioning
confidence: 99%